Quantitative Analysis of Breast Skin for Tumor Detection Using Electromagnetic Waves - Woten, D. A.; Shenawee, M. El- (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper supplements the existing knowledge on the breast skin’s effect on microwaves for tumor detection in the frequency range 4GHz - 7GHz. A realistic breast model is developed using data of an MRI scan of a physical breast. The breast fibro glandular content along with the tumor’s size and location are considered. Numerical results indicate that the skin and tumor signatures could be on the same order of magnitude. This confirms the need to include the skin layer in breast models to minimize the potential of false alarms in tumor detection.